Utilización de proteína concentrada de soya en la elaboración de alimentos preiniciadores para lechones - Navarro González, Héctor (Universidad de Costa Rica, 2013)
Utilization of soy protein concentrate in piglet prestarted diets.A sirty four percent crude protein soy protein concentrate wasevaluated as a substitute protein for dry skimmed mitk in prestarter diets fed to piglets from 2r to 42 days of age. Foriy percent of the original protein content in the contror diet was supptied with dry skimmed milk and substituted in s3, 66 and 100 percent of its totat content by the soy concentrate protein to form the other three experimental diets. No statistical difference was obserued in feed consumption, daily weight gain and feed conversion (p20.05) within each week period between the controt diet and the three experimental diets. The utilization of a soy protein concentrate used as a substitute for dry skimmed milk is a nutritionally and economically feasible alternative in prestarter diets without affecting the piglet perlormance. Further studies should be conducted.